Polak o celtach, czyli uwagi własne o demitologizacji wybranych cech wizerunkowych Irlandii i Irlandczyków .......... 161 - Konarski, Wawrzyniec (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
POLE ABOUT CELTS, THAT IS OWN COMMENTS ON DEMYTHOLOGIZATION OF SELECTED IMAGE FEATURES OF IRELAND AND IRISHThe perception of the Irish by Poles includes a significant number of superficial opinions, based on repeated myths. Interest towards Ireland demonstrated by Poles has intensified since 2004, i.e. since Poland became a full member of the European Union. This fact initiated the emigration of tens of thousands of Polish citizens to Ireland. As time passed, the hitherto little-known Ireland (both its independent part and the one still being a British province, i.e. Northern Ireland) gained the status of an economically but also cognitively interesting area for Polish newcomers. At the same time, the number of people who considered themselves experts in Irish history, literature, music, economics or politics began to increase. At the same time, they most often referred to issues intended to emphasize the similarities between the two nations, while ignoring potential differences. This fostered the strengthening of mutual stereotypes based on historical myths, which, however, had little to do with their deeper analysis. Following this line of reasoning, this text is an attempt to partially restore the necessary proportions by departing from the superficial judgments about Ireland and the Irish proclaimed – present not only in Poland. Their demythologization naturally deserves a more extensive research. However, due to the volume limitations adopted here, I exemplify only selected areas which are recalled and referred to the Irish experiences. They are: nation and nationalism, as well as the state and the Roman Catholic Church.